The Auditory Intelectual Repetition (AIR) Learning Model to Improve Mathematics Problem Solving Ability in Elementary School - Miqkial Wirna; Rusdial Marta; M. Syahrul Rizal; Fadhilaturrahmi Fadhilaturrahmi; Mufarizuddin Mufarizuddin (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to improve the mathematical problem-solving skills of fifth grade students of UPT SDN 004 Pulau Terap for the 2022/2023 academic year, with a total of 15 students. This type of research is Classroom Action Research which is carried out in 2 cycles, each cycle being held in 2 meetings. Data collection was carried out by testing problem solving abilities. Teacher and student observation sheets as the level of implementation and achievement in using the Auditory Intellectually Repetition learning model. The results of problem solving abilities can be seen from the results of the pre-cycle, cycle I and cycle II tests. In the pre-cycle test the average score was 57.72 with a learning completeness percentage of 33.33%, in the first cycle test the first meeting increased with an average student score of 65.99 with a learning completeness percentage of 53.33% and in the first cycle the second meeting also experienced an increase with an average score of 74.21 with a learning completion percentage of 66.67%. In the second cycle the first meeting experienced an increase with an average score of 77.93 with a learning completeness percentage of 73.33%, and in the second cycle the second meeting experienced an increase with an average value of 85.38 with an 80% learning completeness presentation. Based on the research results, it can be concluded that the Auditory Intellectually Repetition learning model can improve students' mathematical problem solving abilities in spatial construction material in class V UPT SDN 004 Pulau Terap. Keywords: Problem Solving Ability, Auditory Intellectually Repetition Learning Model, Mathematics